Moving to free software - Gagné, Marcel (Addison Wesley Professional, 2006)
Stop paying for Windows software! There are free alternatives that are just as good ... even better! In Moving to Free Software, world-renowned open source software expert Marcel Gagne tours the little-known world of free Windows software, uncovering today's best packages for everything you'll ever want to do with your PC! You'll discover amazing tools for everything from Web browsing to instant messaging, office productivity to gaming, and even Windows security. You won't see this software advertised in fancy magazines, or on TV ... it's the best kept secret in computing! Surf the Web safer, faster, and smarter with Firefox Get free Spam filtering and advanced email security with Thunderbird Discover OpenOffice.org 2.0, today's super-powered office productivity suite Get free instant messaging that talks to AOL, ICQ, Yahoo!, and MSN Make free calls anywhere on Earth, with Skype Create podcasts (and more) with Audacity ... or download podcasts with Juice Build your own Web site with NVU Create and edit digital art with Inkscape and The GIMP Protect your Windows computer with Spybot and ClamWin Discover great free games, including Flightgear, the better flight simulator There's more--from handy utilities like CD Ripper to pro-quality desktop publishing software for all your newsletters and brochures. This book gives you software the way it's supposed to be--powerful, friendly, and free!